Readiness factor identification Bandung city MSMEs use blockchain technology - Wahyuni, Ayu Endah; Juraida, Anita; Anwar, Asep (Universitas Serang Raya, 2021)
MSMEs in Indonesia are expected to be able to face competition in the era of industrial revolution 4.0. However, there are many problems and obstacles in competitiveness, especially facing global competition, including access to capital, access to information and technology, access to organization and management, and access to business networks and partnerships. Besides, it is often difficult for them to get additional capital through banks or other lenders to increase their business scale. Moreover, a lack of financial and digital literacy causes the low validity of MSMEs' data to lenders. The adoption of blockchain technology is one of the considerations to minimize these MSMEs problems. Meanwhile, this technology is still relatively new to be applied to MSMEs but positively impacts the future. This study aims to measure and analyze MSMEs' readiness in using blockchain technology on a business scale with the TRAM model. This model integrates the Technology Readiness Index (TRI) and Technology Acceptance Model (TAM) models. This study aims to test several variables, including TRI, perceive ease of use, perceive ease of usefulness, attitude toward, and intense use of blockchain technology. Data processing uses the partial least square path modelling (PLS-PM) method. The results showed that TRI was significant on perceived ease of usefulness and perceived ease of usefulness. Then, perceive ease of use is significant towards perceive ease of usefulness and intention to use. Besides, perceive ease of usefulness is significant for attitude. The attitude toward variable is significant for the intention to use in the acceptance of blockchain technology.